Risk Factors On Firm Resilience In Agricultural Sector The Mediating Effect Of Supply Chain Risk Management Practices - Widiyanesti, Sri (2019)
This research is a quantitative study that discusses the effect of governance of risk factor on firm resilience in the Indonesian agriculture industry. This research was conducted because the current conditions of agricultural firms in Indonesia cannot be resilient in the facing of the risks that arise. This research discussed the relationship between risk factor governance and firm resilience, supply chain risk management practices and firm resilience, and risk factors governance and supply chain risk management practices. This research also discusses the influence of mediation risk information sharing and risk sharing mechanism (supply chain risk management practices) on the relationship of risk factor governance with firm resilience. This research was conducted empirically by using 204 agricultural firms in Indonesia which are engaged in nine basic needs of the Indonesian people. This study used Smart PLS-SEM 3.2.7 to test relationship hypotheses. Result from the data analysis, the relationship between risk factor governance and firm resilience, risk factor governance and supply chain risk management practices, is partially significant. Supply chain risk management practices is positively significant with firm resilience. From the result, supply chain risk management practices is partially mediated to the relationship risk factors with firm resilience. Therefore, agricultural firms in Indonesia must give attention to factors that can affect firm resilience.